Answer:
<h2><em><u>
0.6 = 6/10 = 3/5 is the answer.</u></em></h2>
Step-by-step explanation:
0.6 = 6/10 = 3/5
is the answer
This is because you have to substitute.
Given:
x = 3
y = -1
Unknown:
Final Answer
(x*y^2)/5
((3)(-1*-1)/5
= (3*1)/5
<h2><em><u>
= 3/5</u></em></h2><h2><em><u>
= 6/10</u></em></h2><h2><em><u>
= 0.6</u></em></h2><h2><em><u>
</u></em></h2>
Hope this helped,
Kavitha
I believe the answer is 57
Divide $7.80 by 3
gives you $2.6
Answer:
7/8
Step-by-step explanation:
1/2+1/4=3/4
3/4 + 1/8=7/8